PENGALAMAN, KOMPLEKSITAS TUGAS DAN SELF EFFICACY SEBAGAI DETERMINAN SKEPTISISME PROFESIONAL UNTUK MEMBENTUK AUDIT JUDGMENT - Paulus Tangke; Suwandi Ng; Erica Tungabdi (Universitas Agung Podomoro, 2020)
This study aims to analyze the influence of Experience, Task Complexity, and Self Efficacy on audit judgment through Professional Skepticism as an intervening variable. The population in this study is a Public Accounting Firm in Indonesia, which is listed on the Indonesian Public Accounting Firm Directory 2018. The sample in this study was 14 Public Accounting Firm in Sulawesi and using purposive sampling method. Sources of data in this study are primary data collected through questionnaires. This study use multiple linear regression analysis and path analysis.The results showed that experience has a negative and not significant on professional skepticism, task complexity has a negative and significant on professional skepticism, self efficacy has a positive and significant on professional skepticism. Experience, self efficacy, and professional skepticism has a positive and significant on audit judgment. Task complexity has a negative and significant on audit judgment. Professional skepticism can not mediate the relationship between experience on audit judgment. Professional skepticism may mediate the task complexity and self efficacy on audit judgment.